2007
DOI: 10.3390/12030312
|View full text |Cite
|
Sign up to set email alerts
|

Mistletonone, a Novel Antioxidative Diarylheptanoid from the Branches and Leaves of Viscum coloratum

Abstract: Mistletonone, a novel diarylheptanoid, was isolated from the branches and leaves of Viscum coloratum (Kom.) Nakai (Loranthaceae). It was identified as 1,7-di-(phydroxyphenyl)-5-hydroxyl-cis-2,3-epoxy-1-one on the basis of spectral evidence. The compound showed significant scavenging effects on hydroxyl radicals and superoxide anion radicals in the direct assay using the electron spin resonance (ESR) technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Previous phytochemical investigations have revealed that flavonoids, triterpenoids, and organic acids are the major secondary metabolites of this genus . Antioxidative and apoptosis-inducing activities of plants in the genus Viscum have also been reported in recent years. , Free radicals are involved in many disorders such as neurodegenerative diseases, cancer, and AIDS. Antioxidants through their scavenging power are useful for the management of those diseases.…”
mentioning
confidence: 96%
“…Previous phytochemical investigations have revealed that flavonoids, triterpenoids, and organic acids are the major secondary metabolites of this genus . Antioxidative and apoptosis-inducing activities of plants in the genus Viscum have also been reported in recent years. , Free radicals are involved in many disorders such as neurodegenerative diseases, cancer, and AIDS. Antioxidants through their scavenging power are useful for the management of those diseases.…”
mentioning
confidence: 96%
“…The first naturally occurring diarylheptanoid, curcumin, a yellow dye of the Curcuma species, was reported in the early 1800s ( Keserü and Nógrádi 1995 ). Diarylheptanoids have been reported to have a variety of therapeutic actions in vitro such as inhibition of platelet aggregation ( Doug et al 1998 ), antioxidation ( Yao et al 2007 ), antiinflammation ( Sodsai et al 2007 ), and antitumor-promoting effects ( Chun et al 1999 ; Lee et al 1998 ). Because Curcuma comosa Roxb., an indigenous medicine, has estrogen-like activity ( Piyachaturawat et al 1995a , 1995b ) and has been extensively used among menopausal women, it is essential to characterize its biological action to avoid any risk that may occur from chronic consumption or environmental exposures.…”
mentioning
confidence: 99%
“…Studies have reported the free oxygen radicals scavenging activity of curcumin (Unnikrishnan and Rao, 1995;Jayaprakasha et al, 2006;Ak and Gülçin, 2008). Mistletonone exhibited scavenging capability both on hydroxyl radicals and superoxide anion radicals as compared with standard (−)-epigallocatechin gallate (Yao et al, 2007). Cassumunin A, B, C and cassumunarin A, B, C isolated from Zingiber cassumunar are also potent antioxidants showing stronger or equal antioxidant activity as that of curcumin (Nagano et al, 1997;Masuda et al, 1995).…”
Section: Anti-oxidant Activitymentioning
confidence: 99%